Tratamentos adsortivos e de oxidação avançada de fenol, 2-nitrofenol e 4-nitrofenol em solução aquosa - Nogueira, Maria Ionete Chaves (2009)
In the present work the batch adsorption and advanced oxidation of phenol (F), 2-nitrophenol (2NF) and 4-nitrophenol (4NF) in aqueous phase has been studied. The adsorption experiments were conducted onto coconut shell powder (BIN), coconut shell powder treated with HCl 1.0M (BT) and coconut shell-based activated carbon (CA) obtained from carbonization at low temperature (250°C). Equilibrium and kinetic studies were carried out at temperatures of 28, 40 and 50ºC. Langmuir and Freundlich isotherms correlated well the equilibrium data, indicating the adsorption capacity (qmax) increased in the order: AC>>> BT> BIN. This behavior denotes an adsorption characterized by dispersive interactions between the -electrons of the graphitic carbon basal planes and those of the aromatic rings of the adsorbate, which is more intense when compared to the cellulose materials where are dominant the donor-acceptor complex formation between the oxygenated sites onto adsorbent and aromatic rings of phenol compounds. The best results of qmax in activated carbon and coconut shell powder treated with acid were obtained for the adsorption of 2-nitrophenol at room temperature (28ºC), corresponding to values of 17.1 and 1.39 mg/g, respectively. In all cases, the adsorption kinetics could be satisfactorily fitted by a pseudo-second order model. Advanced oxidation processes (AOP) were carried out for treatments such photolytic (UV), photochemical (UV/H2O2), Fenton (Fe2+/H2O2) and electrochemical oxidation with dimensionally stable anodes (DSA) type Ti/Ru0.3Ti0.7O2, Ti/Ru0.3Ti0.4Sn0.3O2 and Ti/Ru0,3Sn0,7O2. The Fenton and photoassisted tests were performed to optimized conditions of 1.0 mM of Fe2+ ions, 3.0 mM of H2O2 and radiation intensity (I0) of 64 mW/cm2. Particularly, electrocatalytic oxides were prepared by thermal decomposition of chloride precursors to 500oC until the formation of films with thickness constant of 2μm on titanium support. The characterization by EDX, SEM and Cyclic Voltammetry techniques showed a nearly stoichiometric composition, morphology type “cracked mud” and elevated overpotencial from oxygen evolution reaction (OER). Degradation efficiencies in photoassisted processes were particularly high (> 80%) while in the Fenton system this values ranged between 60 and 78%. The kinetic modelling using the equation of pseudo-first order adopted allowed a good fit of experimental data. The values of kinetic constant 1/ (min-1) at room temperature showed the following order: Fenton (8.16 min-1) > Photochemical (6.95 min-1) >> photolytic (1.98 min-1). In addition, studies using the electrocatalytic anodes at constant potential electrolysis of 2.0 V showed almost total degradation for the nitrophenols (> 93%) and moderate removal efficiencies for phenol (between 65 and 86%). In terms, considered the type of anode employed the electrooxidation efficiency at room temperature increase in the following order of reactivity: Ru0.3Ti0.7O2 > Ru0.3Ti0.4Sn0.3O2 > Ru0.3Sn0.7O2. Thus, the results confirm the applicability of adsorption and advanced oxidation processes as promising treatments in the remediation of aqueous systems containing phenol and nitrophenols